IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN TEKS CERITA PENDEK SISWA KELAS XI SMA NEGERI 1 KARANGANYAR - Arfika Dhea Syaharani; Nugraheni Eko Wardani (Universitas Batanghari, 2025)
This study aims to (1) describe the learning planning of short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar, (2) describe the implementation of learning short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar, (3) describe the obstacles faced by teachers in the implementation of learning short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar, and (4) describe the solutions applied by teachers in the implementation of short story text learning with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar. The data sources of this research include documents in the form of teaching modules prepared by Indonesian teachers in class XI F 2, the learning process of short story texts in class XI F2 which implements the Merdeka Curriculum at SMA Negeri 1 Karanganyar, field notes from observations, and informants (Indonesian teachers in class XI F 2). This study uses a qualitative descriptive method with a single embedded case study approach. The sampling technique was carried out by purposive sampling. The results of this study are as follows. First, the learning planning of short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar is not in accordance with the guidelines given by the government related to the learning planning of the Merdeka Curriculum. Of the four stages of learning planning, teachers only apply learning planning in the form of formulating learning objectives and preparing teaching modules. Second, the implementation of learning short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar has a suitability with the teaching modules prepared by teachers. Third, obstacles related to learning short story texts with the Merdeka Curriculum in grade XI of SMA Negeri 1 Karanganyar there are several obstacles faced by teachers. Fourth, teachers have found solutions related to the obstacles they face, in the form of preparing teaching materials for short story texts in advance, stimulating students' ideas, and overseeing each phase of learning.